Suzanne Pepper, China's Universities: Post Mao Enrollment Policies and their Impact on the Structure of Secondary Education. Ann Arbor, Center for Chinese Studies, The University of Michigan, 1984. 155 pp. - Botton Beja, Flora (Estudios de Asia y África, 1986)
-